The effect of TRX and bodyweight training on physical fitness and body composition in prepubescent soccer athletes - Fayazmilani, R.; Abbasi, A.; Hovanloo, F.; Rostami, S. (Sport Sciences for Health, 2022)
Background Resistance training is now highly recommended for enhancing physical fitness in preadolescence. According to this critical period of development, choosing the safe and efficient types of training is important.